China’s chrysanthemum in the global market: evaluating the international competitiveness and influencing factors - Bo Pan; Bo Pan; Yingxin Du; Qingbing Chen; Qingbing Chen; Yaoyao Wang; Lijie Chen; Lijie Chen; Haiying Li; Conglin Huang; Kang Gao (Frontiers in Sustainable Food Systems)
China, with a long history of cultivating chrysanthemums, is one of the largest producers of cut chrysanthemums in the world. The changes in its export volume of cut chrysanthemums directly affect the supply in the international flower market and exert competitive pressure on other exporting countries of cut flowers. This study characterizes the growth, composition and performance of China’s cut chrysanthemum in the global market using various measures and analytical tools, and provides an empirical investigation on the influencing factors of China’s export competitiveness of cut chrysanthemum. The results show that over the past 16 years, China’s export of cut chrysanthemums has maintained a competitive advantage that peaked in 2019, followed by a gradual decline. Market effects and overall competitiveness had the most significant impact on China’s cut chrysanthemum export growth. China’s export of cut chrysanthemums is associated with the number of new varieties, and China exports more cut chrysanthemums to countries with larger population size, more geographical proximity, and closer diplomatic relations. While we do not find significant effect of the Belt and Road Initiatives, we find that Chinese exporters of cut chrysanthemums tend to choose to export to China’s partners of free trade agreement. This study then provides policy suggestions regarding enhancing the international competitiveness of China’s cut chrysanthemums including promoting innovation strengthening international cooperation.